The Urban Imperative : Towards Competitive Cities - Glaeser, Edward (New Delhi: Oxford University Press, 2016)
The volume emphasizes the need to rethink cities and to imagine a better urban future by providing the reader with diverse perspectives on urbanization such as the changing economic landscape, city competitiveness, entrepreneurship, inclusion, informality, sustainability, and provision of essential services.